Large-scale underground construction risk assessment using decision aids for tunneling (DAT) - Tan, Julia Chu Quan (2017)
The Final Year Project (FYP) covers the need for risk analysis, types of risk particularly in construction projects, and further discusses on the use of the Decision Aids for Tunneling (DAT) for underground construction projects. It includes the review of basic underground construction methods, and goes further in depth to share the process of the DAT simulation. In this report, the risk analysis of an ongoing large scale underground project will be carried out via the DAT simulation. Steps wise procedure in the DAT simulation will be carefully explained in Chapter 3, and the results are then compared with the results from @Risk, a generic risk analysis program that has been used more commonly, but is unable to achieve a holistic risk analysis for large scale underground projects. Finally, after studying the risk analysis results from both DAT and @Risk, the potentials of DAT will be discussed.